CYTOKINE STATUS IN HYPOCHROMIC ANEMIAS OF DIFFERENT GENESIS - Суржикова, Галина Северьевна; Клочкова-Абельянц, Сатеник Аршавиловна; Филимонов, Сергей Николаевич (Medicine in Kuzbass, 2020)
Objective – to study the cytokine status of blood serum in hypochromic anemias of various origins. Methods. The studies were carried out in 396 women aged 16 to 60 years. 79 of them were practically healthy and constituted a control group. 317 had anemic syndrome, 103 of them suffered from iron deficiency anemia, 214 – from chronic diseases. Results. The study of the level of proinflammatory cytokines in persons with ACD revealed an increase in the level of IL-6, TNF-α and interferon-γ, and a pronounced correlation was established between the level of pro-inflammatory cytokines and the content of hepcidin. Conclusions. In hypochromic anemias, a significant increase in proinflammatory cytokines was revealed in persons with anemia of chronic diseases, which leads to a decrease in the availability of iron for erythropoiesis and the formation of functional iron deficiency, in contrast to true iron deficiency in iron deficiency anemias. The approaches to the treatment of these anemias (ACD and IDA) are fundamentally different and this explains the importance of the differential diagnosis of these anemias.